Partisipasi Politik dan Kategorisasi Partai Politik - Dila Sapitri; Sinar Kumala; Nazwan Aulia; Neyra Shaffa Husain (Indo Publishing, 2026)
This study aims to examine the correlation between levels of public political engagement and the classification of political parties within a democratic framework. This study examines how the ideology, social base, and policy orientation of political parties can influence the level of citizens’ engagement in the political process. The methodology employed is qualitative, utilising a literature review that analyses various scientific sources, documents, and relevant literature to achieve a comprehensive understanding. The research findings indicate that political parties characterised by a clear ideological identity, a robust organisational structure, and openness to public aspirations are more likely to enhance citizens’ political engagement. Conversely, parties that lack transparency regarding their actions and fail to consistently fulfil their promises may erode public trust and participation. Furthermore, it was found that political education and access to information are key drivers in boosting public participation. This research enriches the field of political science, particularly regarding the strategic role of political parties in facilitating democratic participation. In practice, these findings can assist policymakers in formulating strategies to strengthen democracy by bolstering political parties and empowering the public in a sustainable manner.